2004
DOI: 10.1007/bf03043229
|View full text |Cite
|
Sign up to set email alerts
|

North Sea hydrodynamic modelling: a review

Abstract: Senckenbergiana m a r i t i m a] 34 ] (1/2) ] 5 3 -8 8 I Frankfurt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 121 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Skogen and Moll (2005) showed that the choice of the physical model is decisive in determining the response of a coupled ecosystem model. In their review on hydrodynamical models Lenhart and Pohlman (2004) referred to a number of studies, where the performance of a biological model is strongly dependent on the performance of the underlying physical model. These authors also stress the need for reliable data on boundary conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Skogen and Moll (2005) showed that the choice of the physical model is decisive in determining the response of a coupled ecosystem model. In their review on hydrodynamical models Lenhart and Pohlman (2004) referred to a number of studies, where the performance of a biological model is strongly dependent on the performance of the underlying physical model. These authors also stress the need for reliable data on boundary conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a long history of modelling the North Sea involving all surrounding nations, ranging in complexity from barotropic tidal and storm surge models to 3D baroclinic models with ecosystem components. Reviews of hydrodynamic modelling in the North Sea are given by Jones (2002), Lenhart and Pohlmann (2004), Delhez et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…can explain the different model results, nor is the RMSE a reliable measure of such comparisons if long time periods are not considered, i.e., at least one calendar year [5,21]. The various hydrodynamic models are developed for different purposes, leading to different formulations and different implementations [22].…”
Section: Introductionmentioning
confidence: 99%